Corporate Social Responsibility and Zakat: A Model of Philanthropy in the Society Era 5.0 - Willya Achmad; W, R Willya Achmad (Sean Institute, 2022)
Corporate Social Responsibility (CSR) and the company's zakat program are two instruments for distributing social responsibility funds, both of which have a religious and state legal basis. Zakat and CSR generally have the same vision and mission, namely concern for overall social conditions. This research was conducted by conducting a literature search relevant to several previous research results, especially those related to the CSR model and zakat philanthropy. The search was carried out through electronic databases such as (Pubmed, Science Direct and Google Scholar), and the results of this study explained that, basically the CSR concept developed in Islamic teachings itself is identical to the conventional philanthropy concept, this can be seen from the teachings of tithe,tithe, and charity without asking for anything in return (qardh). There is no difference between Islamic teachings and the concept of CSR because it has a clearand humane codification of ethics and mechanisms. CSR can be defined as a charitable or philanthropic activity carried out voluntarily by a company as a form of service to the surrounding environment. In simple terms, Corporate Social Responsibility (CSR) is a manifestation of an economic development policy approach oriented towards a sustainable development system. Of course, in this case, zakat and CSR are two interrelated things because CSR will reveal the amount of zakat funds that have been managed and utilized by a company for its activities.